Research for Advancement for Environmental Monitoring using Internet of Things (IoT) - Rutuja Jadhav; Sudeepta Banerjee (Publication of the International Journal and Academic Research, 2025)
The rapid advancement of Internet of Things (IoT) technology offers significant potential for environmental monitoring systems. This study investigates IoT applications in environmental monitoring through a specific case study of air quality monitoring in urban areas. Using a methodology combining literature review and MATLAB simulation, we developed a hybrid IoT architecture that integrates edge and cloud computing with LoRaWAN sensor networks. Our comparative analysis of Zigbee vs. LoRaWAN protocols reveals key performance differences: Zigbee achieves 250 kbps bandwidth while LoRaWAN operates at 0.3-50 kbps, with latency thresholds below 100ms for real-time alerts and sensor accuracy of ±10% for PM2.5 measurements. Simulation results demonstrate that the proposed IoT system detects air pollution 2 hours faster than traditional manual systems, achieving 20% improvement in sensor accuracy over conventional monitoring approaches. The hybrid architecture enables cost-effective, scalable environmental monitoring with enhanced real-time capabilities for early warning systems and decision support mechanisms.